Heat Shock Proteins: Potential Modulators and Candidate Biomarkers of Peripartum Cardiomyopathy - Chakafana, Graham; Spracklen, Timothy F.; Kamuli, Stephen; Zininga, Tawanda; Shonhai, Addmore; Ntusi, Ntobeko A. B.; Sliwa, Karen (Frontiers in Cardiovascular Medicine, 2021)
Peripartum cardiomyopathy (PPCM) is a potentially life-threatening condition in which heart failure and systolic dysfunction occur late in pregnancy or within months following delivery. To date, no reliable biomarkers or therapeutic interventions for the condition exist, thus necessitating an urgent need for identification of novel PPCM drug targets and candidate biomarkers. Leads for novel treatments and biomarkers are therefore being investigated worldwide. Pregnancy is generally accompanied by dramatic hemodynamic changes, including a reduced afterload and a 50% increase in cardiac output. These increased cardiac stresses during pregnancy potentially impair protein folding processes within the cardiac tissue. The accumulation of misfolded proteins results in increased toxicity and cardiac insults that trigger heart failure. Under stress conditions, molecular chaperones such as heat shock proteins (Hsps) play crucial roles in maintaining cellular proteostasis. Here, we critically assess the potential role of Hsps in PPCM. We further predict specific associations between the Hsp types Hsp70, Hsp90 and small Hsps with several proteins implicated in PPCM pathophysiology. Furthermore, we explore the possibility of select Hsps as novel candidate PPCM biomarkers and drug targets. A better understanding of how these Hsps modulate PPCM pathogenesis holds promise in improving treatment, prognosis and management of the condition, and possibly other forms of acute heart failure.